Noscapine – a Novel Anticancer Drug for the Treatment of Primary/Secondary Brain Tumor - Kumar, S Sathesh (Asian Journal of Pharmaceutics (AJP), 2018)
Glioblastoma multiforme and anaplastic astrocytomas are the most common type of primary brain tumors in adults. Tumor recurrence (96% cases), adjacent to resection margin after surgical resection, is seen calling out for adjuvant therapy. Due to the presence of blood–brain barrier, the current chemotherapeutics are unable to reach the brain tumor. Noscapine, an antitussive pediatric preparation, at higher concentration induces apoptosis and metaphase arrest in dividing cells with minimal or less toxicity in primary and secondary brain tumor. Nanoparticulate-based drug delivery systems have opened new avenues for the treatment of gliomas and other types of brain tumors. Due to small size, nanometric material causes better permeability of therapeutic agents into cells compared to conventional therapy. Nanoparticulate drug delivery systems that are currently under investigation for treatment and diagnosis of primary brain tumor include liposomes, polymeric nanoparticles, quantum dots, and polymeric micelles. Nanoparticles may offer an improvement to nose-to-brain drug delivery since they are able to protect the encapsulated drug from biological and/or chemical degradation and extracellular transport by P-gp efflux proteins. This would increase central nervous system availability of the drug. To achieve the ultimate clinical translation of noscapine nanoparticles delivery system, a great deal of effort through interdisciplinary collaborations will be required to optimize dose, the design of nanocarrier, to improve the bioavailability at target site with minimal toxicity, in vivo pharmacokinetics, and targeting efficacy through intranasal route.